A rare case of cecal volvulus in a pediatric patient with dolichocolon - Emily A. Rinebold; Elizabeth J. Lee; Katarzyna Zaniewska; Kaitlynne N. Cunningham; Francisca Velcek (Elsevier, 2022)
Dolichocolon is an anatomic variant characterized by redundant colon. While the overall incidence of this condition is unknown, cases of dolichocolon resulting in cecal volvulus are rarely reported. A high index of suspicion is required to correctly identify cecal volvulus, regardless of the cause. Mobile redundant colon seen in dolichocolon predisposes patients to volvulus. This case report demonstrates an unusual presentation of cecal volvulus in a healthy adolescent with previously undiagnosed dolichocolon. This unusual case provides diagnostic clues to identify dolichocolon and resultant volvulus in an otherwise healthy adolescent boy.